Gender diversity and board performance: women's experiences and perspectives - Kakabadse, Nada K.; Figueira, Catarina; Nicolopoulou, Katerina; Hong Yang, Jessica; Kakabadse, Andrew P.; Özbilgin, Mustafa F. (Wiley, 2015)
Despite considerable progress that organizations have made during the past 20 years to increase the representation of women at board level, they still hold few board seats. Drawing on a qualitative study involving 30 companies with women directors in the United Kingdom, the United States, and Ghana, we investigate how the relationship between gender in the boardroom and corporate governance operates. The findings indicate that the presence of a minority of women on the board has an insignificant effect on board performance. Yet the chairperson's role is vital in leading the change for recruiting and evaluating candidates and their commitment to the board with diversity and governance in mind. Our study also sheds light on the multifaceted reasons why women directors appear to be resisting the discourse of gender quotas.